Basic immunology functions and disorders of the immune system - Abbas, Abul K.; Lichtman, Andrew H. (Saunders/Elsevier, 2016)
In this updated edition of Basic Immunology, the authors continue to deliver a clear, modern introduction to immunology, making this the obvious choice for today's busy students. Their experience as teachers, course directors, and lecturers helps them to distill the core information required to understand this complex field. Through the use of high-quality illustrations, relevant clinical cases, and concise, focused text, it's a perfectly accessible introduction to the workings of the human immune system, with an emphasis on clinical relevance